Influence of glucose-6 phosphate dehydrogenase (G6-PD) deficiency upon clinico-haematological and biochemical expression of patients with sickle cell disease - Memon, Mohd. Jafar; Gahine, Renuka; Hussain, Nighat; Gupta, Yashita (International Journal of Advances in Medicine, 2017)
Background: According to world health organization, G6PD deficiency constitute 7.5% of world population as carriers whereas 2.9% as deficient. It has been reported from India that the prevalence varies from 0-27% in different caste, ethnic and linguistic groups. Various studies have revealed strong interaction between G6PD deficiency and sickle cell genes on one hand and environment on the other, one may therefore expect changes in their frequencies over a period of time in the population. We studied the influence of G6PD deficiency upon the clinico-haematological and biochemical expression of sickle cell disease. Methods: The study was carried out prospectively from September 2010 to August 2011 in the department of Pathology at our institute. The material for the present study consisted of 100 cases including 76 patients with Sickle cell disease and 24 of control group. On all the samples after screening and confirmatory tests, hematological and biochemical tests were performed and discussed along with their clinical profiles. Results: A total of 100 patients were studied, 76 were of sickle cell disease and remaining 24 patients were of control group. Majority of sickle cell trait (AS) patients (55.6%) and control patients (54%) had mild anaemia while most of the sickle cell anemia (SS) patients (44.4%) had moderate anaemia. The 2 (100%) AS and 1 (100%) control G6PD deficient patients had moderate anemia while the 2 (100%) SS patients with G6PD deficiency had severe anemia. All the sickle cell disease and control patients with G6PD deficient had elevated serum bilirubin and in all of them only unconjugated bilirubin was raised. None of the SS patients were asymptomatic. All the G6PD deficient patients had pallor and icterus. Vaso-occlusive crisis, acute chest syndrome and infectious episode were present in one (50%) each of AS and SS patients with G6PD deficiency. Conclusions: G6PD deficiency neither exacerbated nor mitigated the frequency of painful crisis, incidence of infection or anemic episodes in patients with sickle cell disease. Hematologically no significant differences were observed in sickle cell disease patients (AS and SS) with G6PD deficiency as compared to sickle cell disease patients without G6PD deficiency and the control.